PROFIL KEMAMPUAN PENALARAN ANALOGI MATEMATIS SISWA SMA PADA MATERI BANGUN RUANG SISI LENGKUNG - Mutiara Sakinah; Dori Lukman Hakim (IKIP Siliwangi, 2023)
Mathematical analogy reasoning ability can help students solve two math problems that have the same concept but with different problem forms. Therefore, this article aims to reveal and describe the mathematical analogy reasoning abilities of high school students in solving curved side geometrical problems. This research is a qualitative research with descriptive method. The subjects used were 3 students out of 30 students in class X-3 SMA Negeri 2 Karawang which were obtained from the results of categorizing mathematical analogy reasoning abilities. The data collection technique used was a written test. This ability is measured based on the stages of analogical reasoning, namely encoding, inferring, mapping and applying. Then data analysis is carried out by reducing data, presenting data, and making conclusions. The results of this article show that of the three subjects who can fulfill the stages of encoding, inferring, mapping and applying, only KA students. NZ students are only able to achieve two stages of analogical reasoning, namely encoding and mapping. Meanwhile, VA students have not been able to fulfill all the stages of mathematical analogy reasoning given. Therefore, efforts are needed to improve students' mathematical analogy reasoning abilities.